Characterization of sound absorbing materials used in noise control engineering - COPS, A.; LAURIKS, W. (Archives of Acoustics, 1993)
Sound absorbing materials are extensively used in the field of noise control engineering and architectural acoustics. Indeed they are, for an important part, responsible for the efficient sound insulation of partitions between rooms and of enclosures, for the acoustic comfort in rooms and industrial halls etc. Due to the continuing technological progress, research has been done and is still done in the motorcar, the aerospace and the manufacturing industries and others, to obtain absorbing materials who are simultaneously small in volume, have a low density, are rather cheap and have a good acoustic performance. From the other side it is necessary to develop precise and, from time to time, sophisticated theoretical models which take into account the complex physical phenomena of acoustic materials.